The effect of foot reflexology and H7 point acupressure on anxiety in women undergoing amniocentesis - Mahyar Mohammadifard; Mahla Salarfard; Marzieh Samieean (Mashhad University of Medical Sciences, 2022)
Introduction: Most pregnant women are concerned about fetal abnormalities and screening tests. Pharmacological and non-pharmacological methods are used to control anxiety in pregnancy. But, there is still no suitable and ideal strategy to reduce anxiety in pregnancy and childbirth. Therefore, this study was performed with aim to compare the effect of foot reflexology and H7 point acupressure on anxiety in women undergoing amniocentesis. Methods: This clinical trial study was performed in 2020on 84 pregnant women candidates for amniocentesis in sonography clinic in Birjand. Individuals were assigned to three groups: foot reflexology, H7 point acupressure and control. In the intervention groups, foot reflexology in the solar plexus and H7 point acupressure were performed by the researcher once 30 minutes before amniocentesis. Reflexology and acupressure were also performed by mothers during the waiting period for amniocentesis. The control group did not receive any intervention. Data collection tools were demographic and pregnancy questionnaires and Spielberger State Anxiety Scale. The Spielberger state questionnaire was completed before the intervention, immediately after and 10 days after amniocentesis and trait anxiety before the intervention and ten days after amniocentesis. Data were analyzed using SPSS software (version 16) and ANOVA, chi-square, analysis of variance with Bonferroni post hoc test and paired t-test. P<0.05 was considered statistically significant. Results: The results showed that state anxiety immediately and 10 days after amniocentesis was significantly lower in the subjects of foot reflexology and acupressure than in the control group (p <0.001). The mean anxiety score at 10 days after amniocentesis was significantly lower in the acupressure group than in the foot reflexology (p <0.001). Trait anxiety 10 days after amniocentesis was significantly lower in the groups of foot reflexology and hand acupressure than in the control group and also in the group of hand acupressure compared to foot reflexology (p <0.001). Conclusion: Both foot reflexology and H7 acupressure were effective in reducing amniocentesis anxiety separately, but the effect of H7 point acupressure was greater than that of foot reflexology.